Nursing students' reflections on caring for end-of-life patients in a youth volunteer association. (January 2019) - Lian, Zhengmei; Skytt, Bernice; Li, Caifu; Engström, Maria
Abstract: The aim of the study was to describe nursing students' reflections on caring for end-of-life patients in a youth volunteer service. A purposive sample of 11 nursing students in one province in China were interviewed and diaries were collected. The data were analysed using qualitative content analysis. The students described the service as "an empowering care that makes a difference – but not without challenges on different levels". The service was said to provide devoted caring adjusted to the person's need, condition and wishes. According to the students, the service had an impact on them; the internal and/or external support was stimulating and rewarding, whereas deficient support was frustrating and made them feel helpless. They emphasized the need for improvements at different levels. In conclusions, the youth volunteer service empowers both patients and students and can be seen as person-centred care. The students' professional knowledge, skills and ability improved, while these aspects were still perceived as deficient. Appropriate curriculum and training for nursing students are necessary and should be tailored to improving students' caring ability and confidence. Expanding the service was emphasized and suggestions for improvements were identified. Highlights: Students found participation in the service to be rewarding and meaningful. Students improved knowledge, skills, ability – changed attitudes and views on life. Students found the service emotional and not without challenges. More mentoring, knowledge and support are needed. Appropriate curriculum and training for nursing students should be designed.